Anti-CD20 monoclonal antibody (rituximab) therapy in chronic immune thrombocytopenic purpura - Akarsu, Saadet; Kurt, Abdullah; Çitak Kurt, A. Neşe; Aydin, Mustafa; Yilmaz, Erdal (My University, 2006)
Approximately 25-30% of patients with chronic immune thrombocytopenic purpura (ITP) do not respond to established therapeutic regimens (corticosteroids, IVIg, anti-D, splenectomy). The mechanism of action of rituximab (anti-CD20) causes opsonization of B cells, which inhibits macrophage Fc receptor function and clearance of IgG-coated platelets. We report on two children with chronic ITP refractory to corticosteroid, IVIg and anti-D who achieved complete and partial normalization of their platelet counts after treatment with rituximab, 375 mg/m 2 given weekly in four doses. CD20 levels were tested 12 times with flow cytometry during the diagnosis, before each dose of rituximab, and at 3-6 week intervals until the 49 th week. The first dose of rituximab rapidly destroyed the entire circulating CD20+ B cell population. Normal B-lymphocyte counts were observed at the end of the 26 th and 30 th weeks, respectively. No important side effect was observed. Neither viral nor bacterial infections were observed during and after treatment. Rituximab is an effective alternative which can be used safely in the treatment of childhood chronic ITP.
Kronik immün trombositopenik purpurada anti-CD20 monoklonal antikor (rituksimab) tedavisi
Keywords: Anti-CD20; Children; Chronic immune thrombocytopenic purpura; Rituximab